Avaliação da espécie vegetal Croton cajucara Benth como inibidor de biocorrosão em aço carbono Aisi 1020 - Felipe, Maria Beatriz Mesquita Cansanção (2012)
Actually in the oil industry biotechnological approaches represent a challenge. In that, attention to metal structures affected by electrochemical corrosive processes, as well as by the interference of microorganisms (biocorrosion) which affect the kinetics of the environment / metal interface. Regarding to economical and environmental impacts reduction let to the use of natural products as an alternative to toxic synthetic inhibitors. This study aims the employment of green chemistry by evaluating the stem bark extracts (EHC, hydroalcoholic extract) and leaves (ECF, chloroform extract) of plant species Croton cajucara Benth as a corrosion inhibitor. In addition the effectiveness of corrosion inhibition of bioactive trans-clerodane dehydrocrotonin (DCTN) isolated from the stem bark of this Croton was also evaluated. For this purpose, carbon steel AISI 1020 was immersed in saline media (3,5 % NaCl) in the presence and absence of a microorganism recovered from a pipeline oil sample. Corrosion inhibition efficiency and its mechanisms were investigated by linear sweep voltammetry and electrochemical impedance. Culture-dependent and molecular biology techniques were used to characterize and identify bacterial species present in oil samples. The tested natural products EHC, ECF and DCTN (DMSO as solvent) in abiotic environment presented respectively, corrosion inhibition efficiencies of 57.6% (500 ppm), 86.1% (500 ppm) and 54.5% (62.5 ppm). Adsorption phenomena showed that EHC best fit Frumkin isotherm and ECF to Temkin isotherm. EHC extract (250 ppm) dissolved in a polar microemulsion system (MES-EHC) showed significant maximum inhibition efficiency (93.8%) fitting Langmuir isotherm. In the presence of the isolated Pseudomonas sp, EHC and ECF were able to form eco-compatible organic films with anti-corrosive properties